A methodology for defining seismic scenario‐structure‐based limit state criteria for rc high‐rise wall buildings using net drift. (16th December 2016) - Alwaeli, Wael; Mwafy, Aman; Pilakoutas, Kypros; Guadagnini, Maurizio
Summary: As a result of population growth and consequent urbanization, the number of high‐rise buildings is rapidly growing worldwide resulting in increased exposure to multiple‐scenario earthquakes and associated risk. The wide range in frequency contents of possible strong ground motions can have an impact on the seismic response, vulnerability and limit states definitions of RC high‐rise wall structures. Motivated by the pressing need to derive more accurate fragility relations to be used in seismic risk assessment and mitigation of such structures, a methodology is proposed to obtain reliable, Seismic Scenario‐Structure‐Based (SSSB) definitions of limit state criteria. A 30‐story wall building, located in a multi‐seismic scenario study region, is utilized to illustrate the methodology. The building is designed following modern codes and then modeled using nonlinear fiber‐based approach. Uncertainty in ground motions is accounted for by the selection of forty real earthquake records representing two seismic scenarios. Seismic scenario‐based building local response at increasing earthquake intensities is mapped using Multi‐Record Incremental Dynamic Analyses (MRIDAs) with a new scalar intensity measure. Net Inter‐Story Drift (NISD) is selected as a global damage measure based on a parametric study involving seven buildings ranging from 20 to 50 stories. This damage measure is used to link local damage events, including shear, to global response under different seismic scenarios. While the study concludes by proposing SSSB limit state criteria for the sample building, the proposed methodology arrives at a reliable definition of limit state criteria for an inventory of RC high‐rise wall buildings under multiple earthquake scenarios. Copyright © 2016 John Wiley & Sons, Ltd.